Kemampuan Pemecahan Masalah Sebagai Variabel Intervening dalam Korelasi Antara Spiritual Quotient (SQ) dengan Hasil Belajar - Al Ayubi, Sholahudin; Rahayu, Agustina; Siskawati, Fury Styo (Program Studi Pendidikan Matematika FIP UNHASY, 2025)
Abstract Starting from the relationship between students' ability to solve math problems and with spiritual quotient, which relates to inner wisdom, when a student can solve problems. This situation inspires research that aims to find a correlation between exogenous variables, namely spiritual quotient, and endogenous variables, namely problem-solving ability, through the intervening variable, namely learning outcomes. The type of research used is correlational with a quantitative approach. The data collection used is questionnaires, tests, and documentation with instruments in the form of questionnaire sheets, test questions, and learning outcomes data, respectively, with the data analysis method using SEM-PLS. Based on the research conducted, the results obtained are that there is a positive correlation between each variable, both simultaneously and partially. With suggestions that can be conveyed, namely a teacher needs to consider aspects other than cognitive abilities of students in learning, one of which is spiritual quotient, because it also has an impact on the acquisition of learning outcomes Keywords: Spiritual Quotient, Learning Outcomes, Mathematical Problem Solving